Self-Disclosure in Interpersonal Communication on Victims of the Domestic Violence (KDRT) in Medan - Henny Mishbah Liyana; Sakhyan Asmara; Nurbani (Jurnal Multidisiplin Madani, 2024)
This study aims to analyze self-disclosure in interpersonal communication and the causes of the victim's decision to self-disclose, so that the victim filed a complaint against the violence she experienced to the KOMNAS Perempuan Partner Service Institute. The research method used descriptive analysis with a qualitative approach. Data were collected through interviews with eight main informants and six triangulation informants. The results showed that self-disclosure in interpersonal communication was carried out to the people closest to the victim, namely friends, biological mothers, adoptive mothers, nephews, and lawyers who handled the case, by conveying messages in the form of domestic events aimed at getting a way out of solving the problem, through direct and indirect communication channels (WhatsApp), causing effects, namely awareness of the right to protection from the state, the courage to sue and report the perpetrator, get help with case fees, the willingness of the communicant to become a trial witness, and the acceptance of the victim to return to live with the communicant. Two informants were in the open window because they realized the violence they experienced and intended to disclose it, two informants were in the blind window because they did not realize the violence they experienced, and four informants were in the hidden window because they realized the violence they experienced but had hidden it. Self-disclosure was done by four informants openly and four informants covertly